Characteristics Sensory of White Bread Enriched with Various Concentrations of Green Mustard Flour (Brassica Juncea) - Rizka Faticha Sari Rizka; Ida Agustini Saidi; Syarifa Ramadhani Nurbaya; Rahmah Utami Budiandari (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to find out the effect of the concentration of green mustard flour (Brassica juncea) on the characteristics of fresh bread. This study was conducted using a randomized design group (RAK) factorial with the first factor of treatment of the concentration of green mustard flour consisting of 9 levels namely P1 0% Green Mustard Flour, P2 1% Green Mustard Flour, P3 2% Green Mustard Flour, P4 3% Green Mustard Flour, P5 4% Green Mustard Flour, P6 5% Green Mustard Flour, P7 6% Green Mustard Flour, P8 7% Green Mustard Flour and P9 8% Mustard Flour. The variable measured is an organoleptic test of volume, taste, and texture. The results showed that the treatment of the concentration of green mustard flour had a noticeable effect on organoleptic tests (volume, taste, and texture).